Axial structure of hollow cathode DC glow discharge in different burning modes - Lisovskiy, V.A.; Bogodielnyi, I.A.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2013)
The axial profiles of the electron temperature, plasma concentration and plasma potential in a DC glow discharge in nitrogen with a hollow cathode were registered with probe technique. At low pressure (0.05 Torr) the discharge is shown to burn in a high-voltage (electron-beam) mode when an electron beam is formed inside the cathode cavity. A potential barrier is found near the cathode sheath boundary. At gas pressure starting from 0.15 Torr at low discharge currents a glow mode is observed. At higher current the discharge is burning in the hollow mode in which the cavity is filled with high concentration plasma. A potential well up to 3 V deep is observed near the edge of the cathode cavity. On increasing the gas pressure the depth of the potential well in the cathode cavity decreases and the well disappears at 0.5 Torr. Осьові профілі температури електронів, густини плазми і потенціалу тліючого розряду з порожнистим катодом в азоті були досліджені зондовим методом. Показано, що при низькому тиску (0.05 Toрр) розряд горить у високовольтному (електронно-променевому) режимі, коли електронний пучок формується в катодній порожнині. Поблизу межі катодного шару виявлено потенційний бар'єр. При тиску газу, починаючи з 0.15 Toрр, при низьких розрядних струмах спостерігається тліючий режим. При більш високому розрядному струмі розряд горить в порожнистому режимі, в якому порожнина катода заповнена плазмою високої концентрації. Потенційна яма глибиною до 3 В спостерігається в порожнині катода. З підвищенням тиску газу її глибина зменшується, і при 0.5 Toрр яма зникає. Осевые профили температуры электронов, плотности плазмы и потенциала тлеющего разряда с полым катодом в азоте были исследованы зондовым методом. Показано, что при низком давлении (0.05 Toрр) разряд горит в высоковольтном (электронно-лучевом) режиме, когда электронный пучок формируется в катодной полости. Вблизи границы катодного слоя обнаружен потенциальный барьер. При давлениях газа, начиная с 0.15 Toрр, при низких разрядных токах наблюдается тлеющий режим. При более высоком разрядном токе разряд горит в полом режиме, в котором полость катода заполнена плазмой высокой концентрации. Потенциальная яма глубиной до 3 В наблюдается в полости катода. С повышением давления газа ее глубина уменьшается, и при 0.5 Toрр яма исчезает.